TEN YEARS RETROSPECTIVE AUTOPSY STUDY OF THROTTLING AND TRAUMATIC ASPHYXIA - PRATAP SINGH, JASPINDER; KUMAR, KULDIP (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study were to assess the characteristics of wounds on the body if present and to study the effect of constriction externally as well as internally on the underlying structures of the neck in throttling and traumatic asphyxia. Methods: Collection of data was done from the record of the autopsies conducted of cases of traumatic asphyxia and throttling among the violent asphyxial deaths in the mortuary associated with the Department of Forensic Medicine and Toxicology, Government Medical College, Amritsar, during the past 10 years from January 1, 2006, to December 31, 2015. Results: Among the violent asphyxial deaths studied, 5 (1.23%) cases studied were of throttling, 4 (0.98%) cases were of suffocation, and the least common was traumatic asphyxia for which only 3 (0.74%) cases were studied. Out of 5 cases of throttling, mechanical injuries were present in 4 (80%) cases, out of which bruises were seen in 1 (20%) case, while abrasions in combination with bruises were seen in 3 (60%) cases. Among the 3 (100%) cases of traumatic asphyxia, contusion of strap muscles, contusion of sternocleidomastoid, and contusion of subcutaneous tissue of the neck were present in all 3 (100%) cases. Regarding the time since death, the majority of cases of throttling and traumatic asphyxia 4 (50%) cases have 12 to 24 h, followed by two each (25%) have 24 to 36 h and 3 to 7 days. Conclusion: Knowledge of these structures is necessary for the consistent diagnostic challenges associated with throttling, strangulation, and other forms of neck compression.